2021
DOI: 10.1080/14712598.2021.1968825
|View full text |Cite
|
Sign up to set email alerts
|

Luspatercept for β-thalassemia: beyond red blood cell transfusions

Abstract: Introduction: Red blood cell transfusions and iron chelation therapy are the cornerstone of treatment for β-thalassemia, with allogeneic hematopoietic stem cell transplantation and gene therapy offering further disease-management options for eligible patients. With up to 90% of severe cases of βthalassemia occurring in resource-constrained countries, and estimates indicating that 22,500 deaths occur annually as a direct consequence of undertransfusion, provision of adequate treatment remains a major issue. Are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Another unanticipated pathway controlling erythropoiesis has been identified by the use of activin receptor trap ligands (namely sotatercept and luspatercept) that were initially designed to target TGF-ß ligands and improve osteoporosis [ 5 ]. These drugs can increase RBC production in normal individuals and patients affected by β-thalassemia and myelodysplastic syndromes (MDS) by a pathway distinct from that of EPO and affecting predominantly the erythroblasts [ 6 ]. The molecular mechanisms that underlie the activity of activin traps are not clear.…”
Section: Erythropoiesismentioning
confidence: 99%
“…Another unanticipated pathway controlling erythropoiesis has been identified by the use of activin receptor trap ligands (namely sotatercept and luspatercept) that were initially designed to target TGF-ß ligands and improve osteoporosis [ 5 ]. These drugs can increase RBC production in normal individuals and patients affected by β-thalassemia and myelodysplastic syndromes (MDS) by a pathway distinct from that of EPO and affecting predominantly the erythroblasts [ 6 ]. The molecular mechanisms that underlie the activity of activin traps are not clear.…”
Section: Erythropoiesismentioning
confidence: 99%
“…Luspatercept is a novel recombinant protein that preferentially binds to TGF-β superfamily ligands, such as GDF11, GDF8, and activin B, in vivo [ 97 ]. The significant inhibition of the TGF-β signaling promotes the differentiation and maturation of late-stage erythroid precursors such as erythroblasts [ 97 , 98 ].…”
Section: Managementmentioning
confidence: 99%
“…Luspatercept is a novel recombinant protein that preferentially binds to TGF-β superfamily ligands, such as GDF11, GDF8, and activin B, in vivo [ 97 ]. The significant inhibition of the TGF-β signaling promotes the differentiation and maturation of late-stage erythroid precursors such as erythroblasts [ 97 , 98 ]. The BELIEVE study (NCT02604433) in patients with TDT showed a reduction in transfusion burden by at least 33% in patients in the luspatercept group compared with that in the placebo group (70.5% vs. 29.5%) [ 99 ].…”
Section: Managementmentioning
confidence: 99%
“…An appropriate regimen of transfusion therapy and optimal safety of transfused blood are key concepts in protocols developed for routine administration of red blood cells to patients with thalassemia 10 . While the recent introduction of Luspatercept 11,12 gives hopes to many patients, the only treatment that can be considered a cure for β-thalassemia is transplantation of hematopoietic stem-cells (BMT, bone marrow transplantation) 13 . In this procedure, enhanced conditioning regimens on one hand and improved procedures for donor selection on the other led to significant better results when data obtained applying these methods were considered in recent years 14 .…”
Section: Introductionmentioning
confidence: 99%